2024
DOI: 10.1001/jamainternmed.2023.0699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oseltamivir Used to Prevent Hospitalization in Outpatients With Influenza

Abstract: ImportanceDespite widespread use, summary evidence from prior meta-analyses has contradictory conclusions regarding whether oseltamivir decreases the risk of hospitalization when given to outpatients. Several large investigator-initiated randomized clinical trials have not yet been meta-analyzed.ObjectiveTo assess the efficacy and safety of oseltamivir in preventing hospitalization among influenza-infected adult and adolescent outpatients.Data SourcesPubMed, Ovid MEDLINE, Embase, Europe PubMed Central, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Although a meta-analysis of pooled data from underpowered RCTs increases precision, given the very low hospitalization rate (0.6%) among the untreated control population, the total number of participants was still substantially underpowered to assess the benefit of oseltamivir treatment in averting hospitalization. Therefore, the study’s findings were inconclusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a meta-analysis of pooled data from underpowered RCTs increases precision, given the very low hospitalization rate (0.6%) among the untreated control population, the total number of participants was still substantially underpowered to assess the benefit of oseltamivir treatment in averting hospitalization. Therefore, the study’s findings were inconclusive.…”
mentioning
confidence: 99%
“…To clarify whether oseltamivir treatment of outpatients with seasonal influenza reduces the risk of severe disease requiring hospitalization, a sufficiently powered RCT of early oseltamivir treatment vs placebo is needed among outpatients with laboratory-confirmed influenza and increased risk of influenza complications (eg, adults with certain comorbidities, pregnant people, persons aged ≥65 years) . As the authors noted, depending on the expected hospitalization rate, a sufficiently powered RCT would require a minimum of 15 000 to 30 000 participants; ie, more than 2 to 4 times the number of participants included in their meta-analysis.…”
mentioning
confidence: 99%
“…The meta-analysis itself was underpowered to detect an association between oseltamivir and hospitalization . The study compared 3443 oseltamivir-exposed patients vs 2852 unexposed and reported a relative risk (RR) of hospitalization of 0.77 (95% CI, 0.47-1.27).…”
mentioning
confidence: 99%
“…To the Editor On behalf of my coauthors and myself, I write to explain the correction of our Original Investigation, “Evaluation of Oseltamivir Used to Prevent Hospitalization in Outpatients With Influenza: A Systematic Review and Meta-Analysis,” published online first on June 12, 2023, in JAMA Internal Medicine . This systematic review and meta-analysis included data from 15 randomized clinical trials and accurately concluded that oseltamivir was not associated with reduced risk of first hospitalization compared with placebo or standard of care.…”
mentioning
confidence: 99%
“…However, when we received a request to share our study data, we realized that a number of inadvertent transcription and transposition errors had occurred in our response to peer review. These errors were primarily introduced by migrating back and forth between the intention-to-treat and intention-to-treat infected populations for the requested sensitivity analyses; “no hospitalization” and “total population” being transposed in a spreadsheet; and use of different parameters in creating forest plots with the counts as “yes/no” in the latter version vs “yes/total” during drafting.…”
mentioning
confidence: 99%